Management and Bureaucratic Effectiveness : Evidence from the Ghanaian Civil Service - Rasul, Imran (World Bank, Washington, DC, 2018)
A burgeoning area of social science research examines how state capabilities and bureaucratic effectiveness shape economic development. This paper studies how the management practices of civil service bureaucrats correlate to the delivery of public projects, using novel data from the Ghanaian Civil Service. This paper combines hand-coded progress reports on 3,600 projects with a management survey in the government ministries and departments responsible for these projects. The analysis finds that management matters: practices related to autonomy are positively associated with project completion, yet practices related to incentives/monitoring of bureaucrats are negatively associated with project completion. The negative impact of incentives/monitoring practices is partly explained by bureaucrats having to multi-task, interactions with their intrinsic motivation, their engagement in influence activities, and project characteristics such as the clarity of targets and deliverable outputs. The paper discusses the interplay between management practices and corruption, alternative methods by which to measure management practices in organizations, and the external validity of the results. The findings suggest that the focus of many civil service reform programs on introducing stronger incentives and monitoring may backfire in some organizations, and that even countries with low levels of state capability may benefit by providing public servants with greater autonomy in some spheres.